2009
DOI: 10.1039/b814566k
|View full text |Cite
|
Sign up to set email alerts
|

A redshifted codon-optimized firefly luciferase is a sensitive reporter for bioluminescence imaging

Abstract: Bioluminescence imaging has evolved as a powerful tool for monitoring biological processes in vivo. As transmission efficiency of light through tissue increases greatly for wavelengths above 600 nm we examined whether a redshifted codon-optimized firefly luciferase (lambdamax=615 nm) could be successfully employed as a sensitive reporter in mammalian cells. To this end, unmodified codon-optimized luciferase (lambdamax=557 nm) as well as the red-emitting S284T mutant luciferase were expressed simultaneously in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…Data reported the mean percentage of six different red and green tumors. This result is in agreement with previous evidence that light emitted from red-shifted luciferase passes through tissues three times more efficiently than does green light [13].…”
Section: Scarification Studies To Compare Red and Green Signal Absorpsupporting
confidence: 93%
See 1 more Smart Citation
“…Data reported the mean percentage of six different red and green tumors. This result is in agreement with previous evidence that light emitted from red-shifted luciferase passes through tissues three times more efficiently than does green light [13].…”
Section: Scarification Studies To Compare Red and Green Signal Absorpsupporting
confidence: 93%
“…The whole animal BL emission from the HepG2-Ppyred cells was much higher than that obtained from HepG2-Luc, with a mean recovery of the red photons 2:3 AE 0:3 Â 10 5 ph=s=mm 2 ð Þ three times higher than that of the green photons 7:8 AE 0:3 Â 10 4 ph=s=mm 2 ð Þ . These results are consistent with previous experiments, wherein mice were injected with nude plasmids encoding WT luciferase and a red-emitting luciferase (S284T) [13].…”
Section: Bli Of the Hepatoblastoma (Hepg2) Xenograft Murine Model In supporting
confidence: 93%
“…Reprinted with permission (43). modality (7,14). Additionally, alternative methods for transduction of reporter gene may reduce the risk of anomalous and inappropriate transcription of unwanted sequences in mammalian cells (37).…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that human codon optimization of a related red light-emitting luciferase led to a 10-fold improvement in luciferase detectability in the HEK293 cell line (6). The stability of the bioluminescence signal could be improved by insertion of the luciferase reporter gene in the chromosome (20).…”
mentioning
confidence: 99%